Prevalence Of Hypertension and Its Relationship with Overweight and Obesity in Adolescents and Young Adults - Srinivas S; Pallerla, Srinivas; Madoori, Srinivas; Ramdas J; Kotla, Sreenivas; Jalagam, Sandhya Rao (National Journal of Community Medicine, 2015)
Background: The rate of obesity is rapidly rising, and impacting quality of life, psychosocial situation, and health of the affected individual. The purpose of this study was to determine the role of elevated Body Mass Index (B.M.I.) in occurrence of prehyperten- sion and hypertension and their relationship with family history of hypertension among adolescent college students in Hyderabad, Telangana, India. Methods: 1611 students aged between 17 to 25 years of two col- leges which were randomly selected in Moinabad area in out- skirts of Hyderabad, were classified as overweight and obese based on their BMI (BMI ≥ 25kg/m2 and 30 kg/m2 respectively). Subjects were categorised as prehypertensive and hypertensive based on their Blood pressure reading. Results: Prevalence of overweight, obesity, prehypertension and hypertension were 9.15 % 2.11%, 26.95% and 4.86% respectively. Prehypertension and hypertension in males was 35.29% and 6.64% respectively and in females was 9.64% and 1.18% respec- tively. Prevalence of overweight in hypertensive individuals was 16.09 %( p<0.05) when compared in normotensive individuals 5.91%. Prevalence of obesity in hypertensive individuals was 4.22 %( p<0.05), when compared with normotensive individuals was 1.12%. Prevalence of family history of hypertension in hyperten- sive individuals was 43.86%. Conclusion: Prevalence of prehypertension and hypertension were 26.95% and 4.86 % respectively. Our results reinforced that overweight and obesity were to be significantly associated with hypertension.